SALT TEMPLATE-ASSISTED SYNTHESIS OF β-CYCLODEXTRIN DERIVED 3D CARBON NANOCORALS - HUANG, Jinyan; XING, Ye; LI, Haichao (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Carbon nanomaterials have great scientific importance due to their unique physicochemical properties. They show great promise in the fields of catalysis, energy storage and environmental treatment. However, the traditional synthesis methods are characterized by cumbersome steps, difficult template removal and high environmental costs. In this study, a salt template-assisted strategy was innovatively employed with β-cyclodextrin (β-CD) as a renewable carbon source and NaCl as a dynamic separation template. Controlled preparation of 3D carbon nanocorals (CNCs) has been achieved for the first time by regulating the self-assembly and carbonization process. XRD and Raman spectroscopy showed that the graphite microcrystalline ordering of the material increased significantly with increasing concentration, and the graphite layer spacing was reduced from 0.453 nm to 0.443 nm. In addition, the NaCl template has a recovery rate of over 90% after washing. Meanwhile sodium chloride can be reused after recycling. It is in line with the concept of green chemistry. This strategy provides a new idea for the precise construction of complex carbon nanostructures.